The impact of the COVID-19 pandemic on organised cervical cancer screening: The first results of the Slovenian cervical screening programme and registry - Urška Ivanuš; Tine Jerman; Urška Gašper Oblak; Leon Meglič; Mojca Florjančič; Margareta Strojan Fležar; Tanja Premru Sršen; Špela Smrkolj; Maja Pakiž; Maja Primic Žakelj; Veronika Kloboves Prevodnik; Ana Pogačnik; et al. (Elsevier, 2021)
Background: The COVID-19 pandemic threatens the impact of cervical cancer screening and global cervical cancer elimination goals. As cervical cancer screening programmes were adjusting to the new situation, we evaluated the intensity, quality, and outcomes of cervical cancer screening in Slovenia in the first seven months of the pandemic. Methods: Historical observational study on data from a population-based cervical cancer screening registry. Number of cervical cytopathology (screening and follow-up), histopathology (diagnostic procedures, invasive procedures and number of newly diagnosed CIN2+ cases) and HPV test results from the entire Slovenian women population between January 1st and September 30th 2020 were compared to a three-year average of the years 2017-19. Findings: A two-month screening lock-down between March 12th and May 8th 2020 resulted in an epidemic deficit of screening (-92%), follow-up (-70%), and HPV triage tests (-68%), as well as invasive diagnostic (-47%) and treatment (-15%) of cervical lesions. Time to diagnosis and treatment did not increase; times to laboratory results fluctuated but stayed within standards. Slovenia has entered the second epidemic intending to add as little as possible to the pandemic deficit of screening smears (-23%) and yearly CIN2+ cases (-10%). Women aged 30-39 were most affected, with the highest pandemic deficit of screening smears (-26%) and yearly CIN2+ cases (-19%). Interpretation: The pandemic has deeply affected all levels of our lives. New vulnerable groups and inequalities have emerged that require recognition and action. To prevent long-term increases in the cervical cancer burden due to the COVID-19 pandemic, it is crucial that organised screening is maintained and monitored in settings where it can be safely and comprehensively provided. Funding: None.